2021
DOI: 10.1007/s11356-021-12556-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of COVID-19 on Victoria, Australia, witnessed two waves of Coronavirus

Abstract: The COVID-19 pandemic not only has created a global health crisis but also has dramatic effects on the environment. To fight the spread of Coronavirus, governments imposed social distancing policies, which caused negative and positive impacts on the environment. Victoria, the second-most populated state in Australia, was hit by two waves of COVID-19. During the second wave of the pandemic, Victoria, especially Melbourne, experienced one of the most stringent and longest lockdowns globally. In this study, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 27 publications
1
62
0
3
Order By: Relevance
“…Research focusing on South Asia critically investigated lockdown effects toward concentrations of air pollutants and found that a significant reduction of air quality index (AQI) was observed over most polluted ranked cities like Delhi, Dhaka, Kathmandu, Colombo due to the total shutdown [ [20] , [21] , [22] , [23] ]. Similar results have also been found at the all-countries level [ 24 ] such as Australia [ 25 ], UK [ 26 ], Italy [ 27 ], Spain [ 28 ], and Brazil [_Nakada_and_Urban_2020]. Above all, existing research mainly focuses on the air pollution change during the earlier stage of the COVID-19.…”
Section: Introductionsupporting
confidence: 68%
“…Research focusing on South Asia critically investigated lockdown effects toward concentrations of air pollutants and found that a significant reduction of air quality index (AQI) was observed over most polluted ranked cities like Delhi, Dhaka, Kathmandu, Colombo due to the total shutdown [ [20] , [21] , [22] , [23] ]. Similar results have also been found at the all-countries level [ 24 ] such as Australia [ 25 ], UK [ 26 ], Italy [ 27 ], Spain [ 28 ], and Brazil [_Nakada_and_Urban_2020]. Above all, existing research mainly focuses on the air pollution change during the earlier stage of the COVID-19.…”
Section: Introductionsupporting
confidence: 68%
“…In Australia, Beck and Hensher evaluated the effects of working from home on commuting travel behavior, concluding that “working from home will be a key determinant on commuting behavior” Beck and Hensher (2020, p. 16) . Another Australian study presented the impact of the second wave of the pandemic on human mobility, showing a 73–85 percent reduction of traffic in PT hubs in the cases considered ( Boroujeni et al, 2021 ). For the post-pandemic period, an estimation on the number of daily public transport trips to be serviced after COVID-19 is given by the ITF/OECD (2020) ; in some cities, teleworking was anticipated to cause a 30 percent reduction in trips.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Protective measures have a direct or indirect environmental impact (Boroujeni et al 2021 ) and Fig. 5 shows how these measures affect the environment (Rume and Islam 2020 ).…”
Section: Symptoms Severity and Transmission Of Different Variants Of Sars-cov-2mentioning
confidence: 99%
“…Personal protective equipment (PPE) is now required or recommended in nearly every country to help combat the global spread of the SARS-CoV-2 (Boroujeni et al 2021 ). The waste management system has been overwhelmed by single-use plastics, including massive amounts of PPE (Klemeš et al 2020 ).…”
Section: Symptoms Severity and Transmission Of Different Variants Of Sars-cov-2mentioning
confidence: 99%